Clinical correlation of platelet indices in preeclamptic patients without HELLP syndrome - Pankaj Salvi; Vidya Gaikwad; Rashida Ali (Barpeta Obstetrics and Gynaecological Society, 2022)
Objectives: To understand the relationship between the indices of platelet with preeclampsia and to determine if these parameters may be used for early diagnosis. Methods: A prospective case-control study was done on 50 women and they were divided into two groups - the non-severe preeclampsia group (n=36) and the severe preeclampsia group (n=14). Platelet indices - platelet count, mean platelet volume, platelet distribution width, platelet crit and platelet large cell ratio were analyzed and correlated with the observed clinical severity status, organ system affected and feto-maternal outcomes. Results: Findings showed that there was a statistically significant decrease in platelet count (p<0.001) and an increase in mean platelet volume (p<0.001) and platelet distribution width (p<0.05) in mothers of severe preeclampsia group as compared to non-severe preeclampsia group. In the severe preeclampsia group, two out of 14 mothers had abnormal maternal outcomes and all 14 babies were abnormal. Furthermore, platelet count was significantly decreased and plateletcrit was non-significantly decreased in the abnormal maternal prognosis group of mothers. Also, mean platelet volume and platelet distribution width were significantly (p<0.001) increased in the abnormal maternal prognosis group of mothers. Conclusion: As pregnancy advances, the platelet counts decrease while mean platelet volume and platelet distribution width increase, and these kinds of changes are more evident in severe preeclampsia mothers than in non-severe preeclamptic mothers. Thus, platelet indices could be used as biomarkers for early diagnosis of the severity of preeclampsia.